Acute Exacerbation of Cold Agglutinin Disease by SARS-CoV-2 Infection: A Rural U.S. Hospital Experience - Jackson Musuuza; Gilbert-Roy Kamoga; Neelima Gonugunta; Janani Baskaran (Annals of Internal Medicine: Clinical Cases)
COVID-19 has been associated with profound hematologic disease processes, including cold agglutinin disease (CAD). We discuss a patient with preexisting stable CAD that was exacerbated by COVID-19. Management of this patient was complicated by the fact that rituximab, a known therapy for CAD, could not be used. Recent reports have shown poorer survival for patients with COVID-19 who received rituximab. In this report, we discuss the pathogenesis of CAD and its management in the context of SARS-CoV-2 infection. We aim to increase awareness of possible exacerbation of CAD by SARS-CoV-2 infection.